VISUAL STRATEGIES OF CONTEMPORARY ART: A Case Study of Banksy’s Artworks - Singgih Prio Wicaksono (Institut Seni Indonesia Yogyakarta, 2020)
Visual Strategy of Contemporary Art: The Study of Banksy’s Artwork. The development of contemporary art has introduced a new understanding and recognition of esthetics. This article aims to describe postesthetic phenomena as trends in the visual communication of contemporary art. The method used is a descriptive approach and analysis of Banksy's work. This study produces a discussion about: 1). Postesthetic symptoms in Banksy's work, 2). Characteristics of Banksy's work, 3). Banksy's symbolic meaning, 3). Social implications arising from the postesthetic approach to Banksy's work. Keywords: visual language, consumerism, contemporary art